Reaction of 4-Amino-4,5-Dihydro-1H-1,2,4-Triazol-5-one with Some Carboxylic Acid Anhydrides and their Antiinflammatory Activity - Singh, R.J.; Singh, D.K. (Asian Journal of Chemistry, 2010)
Syntheses of a series of 3-alkyl(aryl)-4-tetrachlorophthalimido-4,5- dihydro-1H-1,2,4-triazol- 5-ones and 3-alkyl(aryl)-4-(1,8-naphthalimido-4,5- dihydro)-1H-1,2,4-triazol-5-ones are described. The newly compounds were characterized by spectral and elemental analyses. Some compounds were screened for their antiinflammatory activity. All the compounds carring 1,2,4- triazole moiety showed significant antiinflammatory activity.